The Polish Career of The American Soldier: From the Model to the Legend - Sułek, Antoni (Serendipities. Journal for the Sociology and History of the Social Sciences, 2018)
The study conducted by Samuel Stouffer and his team in the US Army during World War II is generally considered to be a founding study in quantitative empirical sociology. The book The American Soldier (1949-1950) played an important role in the development and institutionalization of empirical social research. Joseph Ryan’s monograph Samuel Stouffer and the GI Survey (2013) analyzes the history and reception of the research and book in the United States. This paper investigates the reception and impact of the book far from the United States: in Poland.